Chronic Ethanol‐Induced Impairment of Wnt/β‐Catenin Signaling is Attenuated by PPAR‐δ Agonist. (23rd April 2015) - Xu, Chelsea Q.; de la Monte, Suzanne M.; Tong, Ming; Huang, Chiung‐Kuei; Kim, Miran
<x xml:space="preserve">Abstract</x> Background The Wnt/β‐catenin pathway regulates liver growth, repair, and regeneration. Chronic ethanol (EtOH) exposure blunts normal liver regenerative responses, in part by inhibiting insulin/IGF signaling, and correspondingly, previous studies showed that EtOH‐impaired liver regeneration could be restored by insulin sensitizer (proliferator‐activated receptor [PPAR]‐δ agonist) treatment. As Wnt/β‐catenin functions overlap and cross talk with insulin/IGF pathways, we investigated the effects of EtOH exposure and PPAR‐δ agonist treatment on Wnt pathway gene expression in relation to liver regeneration. Methods Adult male Long Evans rats were fed with isocaloric liquid diets containing 0 or 37% EtOH for 8 weeks and also treated with vehicle or a PPAR‐δ agonist during the last 3 weeks of the feeding regimen. The rats were then subjected to 70% partial hepatectomy (PH) and livers harvested at various post‐PH time points were used to quantitate expression of 19 Wnt pathway genes using Quantigene 2.0 Multiplex Assay. Results EtOH broadly inhibited expression of Wnt/β‐catenin signaling‐related genes, including down‐regulation of Wnt1, Fzd3, Lef1, and Bcl9 throughout the post‐PH time course (0 to 72 hours), and suppression of Wnt7a, Ccnd1, Fgf4, Wif1, Sfrp2, and Sfrp5 at 18‐ and 24‐hour post‐PH time points. PPAR‐δ agonist treatments rescued the EtOH‐induced suppression of Wnt1, Wnt7a, Fzd3, Lef1, Bcl9, Ccnd1, and Sfrp2 gene expression in liver, corresponding with the improvements in DNA synthesis and restoration of hepatic architecture. Conclusions Chronic high‐dose EtOH exposures inhibit Wnt signaling, which likely contributes to the impairments in liver regeneration. Therapeutic effects of PPAR‐δ agonists extend beyond restoration of insulin/IGF signaling mechanisms and are mediated in part by enhancement of Wnt pathway signaling. Future studies will determine the degree to which targeted restoration of Wnt signaling is sufficient to improve liver regeneration and remodeling in the context of chronic EtOH exposure.